THE EFFECT OF USING SOCIAL MEDIA: WHATSAPP TOWARD THE STUDENTS SPEAKING SKILL - Lusi Marleni; Putri Asilestari (Universitas Pahlawan Tuanku Tambusai, 2018)
The development of technology today makes the learning system for students develop rapidly. One of the media that can be used as teaching material is social media. This study aims to determine the effect of social media: WhatsApp on students' speaking skills. The sample of this study is the second semester class A as the experimental class and the second semester class B as the control class. The research design used is quasi-experimental with purposive sampling technique. The instruments used to collect data are pre-posttest and questionnaire and photo documentation. Based on the results of the study, the average score of students in the experimental class and the control class. After the t-test was obtained a significance (2-tailed) value of 0.000